The Relationship of Social Media Usage and Fear of Missing Out Mediated by Phubbing Behavior - Minhas, Marium Tariq; Gillani, Syeda Asma; Abbasi, Palwasha Nasir (Annals of Human and Social Sciences, 2025)
The relationship between social media use and fear of missing out (FoMO) and phubbing behavior was investigated in this study. Gender differences were also investigated. Social media has a strong influence on behaviors such as phubbing and FoMO. Phubbing, giving smartphone attention over face-time, is largely associated with intensive social media activity and increased FoMO. Addressing these patterns is key to reducing their prevalence among students. A sample of 300 students from Azad Kashmir University was measured on standardized scales of phubbing, social media usage, and FoMO. Data was analyzed using SPSS. The results indicated significant positive correlations between phubbing, social media usage, and FoMO. Significant gender differences were found. Phubbing behavior acted as mediator between FOMO and social media usage.Increasing awareness of the psychological impacts of social media overuse is crucial. Universities must promote healthful digital habits and face-to-face interactions to diminish FoMO.